2013
DOI: 10.1159/000346942
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Tissue Elastography as Promising Diagnostic Tool for Diagnosis of Lymph Node Metastases in Patients with Malignant Melanoma: A Prospective Single-Center Experience

Abstract: Background: Real-time tissue elastography is a new, noninvasive method inultrasonography, differentiating tissues according to their stiffness. Earlier studies have highlighted this technique as a useful diagnostic tool for the detection of noncutaneous malignancies like breast, prostate and thyroid cancer based on the principle that tumor cells present a higher stiffness compared to the adjacent normal tissue. Objective: The purpose of our study was to investigate the value of real-time tissue elastography fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
1
25
0
2
Order By: Relevance
“…Few research studies conducted in the early period of clinical elastography have demonstrated that this technique has potential in the diagnosis of skin tumors. In reported cases the tumors were diagnosed as malignant based on the color distribution on elastographic images [25][26][27]. In this present study, tumor elasticity represented a statistically significant factor: almost half of the tumors were stiff at SE and another important percentage had medium elasticity.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Few research studies conducted in the early period of clinical elastography have demonstrated that this technique has potential in the diagnosis of skin tumors. In reported cases the tumors were diagnosed as malignant based on the color distribution on elastographic images [25][26][27]. In this present study, tumor elasticity represented a statistically significant factor: almost half of the tumors were stiff at SE and another important percentage had medium elasticity.…”
Section: Discussionmentioning
confidence: 51%
“…The use of elastography in the evaluation of skin lesions has been the subject of several studies, in an attempt to differentiate between benign and malignant lesions [25][26][27]. Few research studies conducted in the early period of clinical elastography have demonstrated that this technique has potential in the diagnosis of skin tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Elasticity image of each ablated lymph node had been qualitatively scored for the proportion of stiff areas from score 1 to 5 (soft to stiff) on the basis of a newly defined system for lymph nodes. [12][13][14] Devices for radiofrequency ablation The RFA procedure was performed under real-time ultrasonographic guidance (model: LOGIQ E9, GE Health Care) with 10-MHz linear probe. A18-gauge 7-cm shaft length 0.5 cm straight fixed active-tip electrode with internally cooled (Star RF Electrode-Fixed, STARmed Co., Ltd., Korea) was connected to a radiofrequency generator (VRS01, STARmed Co., Ltd., Korea).…”
Section: Study Populationmentioning
confidence: 99%
“…The technique has been used to assess the hardness of various normal and abnormal tissues, [1][2][3][4][5][6] and to differentiate malignant from benign lesions in the breast, prostate, thyroid, lymph nodes and salivary glands. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ultrasound elastography uses either strain or shear wave velocity. 25,26 In strain elastography, tissue strain induced by compression with the probe is used as an indicator of hardness.…”
Section: Introductionmentioning
confidence: 99%
“…The hardness of tissues or lesions is visually and qualitatively assessed on the basis of the strain distribution and pattern of elastographic images. 1,[6][7][8][9][10]12,[15][16][17][19][20][21][22][23][24] Semi-quantitative analysis, in which strain is represented in numerical values, has recently been used as a more objective method. [1][2][3][4][5][9][10][11]13,17 However, whether these values can be effectively used for clinical assessment remains unclear because the image quality of strain elastography, which is performed manually, depends strongly on the imaging procedure.…”
Section: Introductionmentioning
confidence: 99%